UPAYA PENINGKATAN MINAT DAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN TENTANG MEMAHAMI KEPUTUSAN BERSAMA MELALUI PENDEKATAN PEMBELAJARAN BERBASIS MASALAH DENGAN MEDIA ELEKTRONIK - Tri Haryani (Jurnal Pendidikan Surya Edukasi (JPSE), 2016)
This research has a background is the low value of Civic of the fifth grade students of SD Negeri 2 Sidomoro first semester in district Buluspesantren, Kebumen in the academic year 2014/2015. The purpose of this research is to increase interest and learning outcomes of Civic on understanding the joint decisions through problem-based learning. Kind of research is classroom action with cycle’s method. Subject of research is the fifth grade student of SD Negeri 2 Sidomoro second semesters in the academic year 2014/2015. Collecting data on this research use observation technique. Analysis of data technique that used includes data reduction, data presentation, and conclusion. Researcher use problem-based learning approach to electronic media on first cycle and second cycles with electronic tools. Result of the first test can be seen from the number of 15 students that Civic learning outcomes with a low score 9 students (60%). Five students got middle score (33%) and one student got high score (67%). An average value of learning outcomes is 55. Meanwhile, interest in learning outcomes in the first cycle, first and second meeting as follows: two students get high score (13%), six students get medium score (40%) and janah get low score (47%). High score is 3 students, medium score is 7 students (47%), and low score is 5 students (33%). Meanwhile, learning outcomes reaches an average value of 75. If compare with first meeting in learning outcomes further increased, but does not meet indicators set.  Then, reflection on the results of the second cycle of learning interest, first and second meetings as follows, interest of students who got a high and medium score of six students (40%) and three students got low score (20%). Meanwhile, second meeting is: interest of students study Civic on “Understanding the Joint Decision” that got a high score is 10 students (67%), 5 students got middle score (33%) and there is no student who get low score (0%). Meanwhile, learning outcomes reached an average in the second cycle of 78. Based on result of research can concluded that interest and learning outcomes increased when seen comparisons between the results of the first cycle of both interest and learning outcomes In Civic about understanding the joint decisions through problem-based learning approach to electronic media.